Antibacterial activity of Lavandula hybrida Grosso essential oil associated with cephalothin against Staphylococcus aureus strains (Research, Society and Development, 2021)
The present study to evaluate the antibacterial activity of the essential oil of Lavandula Hybrida Grosso when associated with the antimicrobial cephalothin against strains of Staphylococcus aureus. The antibacterial character of the essential oil of Lavandula Hybrida Grosso was quantified and qualified by the broth microdilution technique to obtain the MIC (Minimum Inhibitory Concentration). Then, the essential oil was combined with the cephalothin antimicrobial (10 μg / mL). The MIC (Minimum Inhibitory Concentration) was 128 μg / mL for the strain under analysis. As for the association, a synergistic effect was observed when associating cephalothin with the essential oil of Lavandula Hybrida Grosso. Therefore, it was observed a synergistic effect of Lavandula Hybrida Grosso essential oil associated with cephalothin against pathogenic strains of S. aureus potentiating its antibacterial pharmacological action. The applicability of phytotherapy based on compounds from medicinal plants is promising in relation to the treatment of bacterial infections, collaborating positively and in conjunction with conventional therapies.